Differential activation of RAW 264.7 macrophages by size-segregated crystalline silica. Issue 1 (December 2016) - Mischler, Steven; Cauda, Emanuele; Di Giuseppe, Michelangelo; McWilliams, Linda; St. Croix, Claudette; Sun, Ming; Franks, Jonathan; Ortiz, Luis
Abstract Background Occupational exposure to crystalline silica is a well-established occupational hazard. Once in the lung, crystalline silica particles can result in the activation of alveolar macrophages (AM), potentially leading to silicosis, a fibrotic lung disease. Because the activation of alveolar macrophages is the beginning step in a complicated inflammatory cascade, it is necessary to define the particle characteristics resulting in this activation. The aim of this research was to determine the effect of the size of crystalline silica particles on the activation of macrophages. Methods RAW 264.7 macrophages were exposed to four different sizes of crystalline silica and their activation was measured using electron microscopy, reactive oxygen species (ROS) generation by mitochondria, and cytokine expression. Results These data identified differences in particle uptake and formation of subcellular organelles based on particle size. In addition, these data show that the smallest particles, with a geometric mean of 0.3 μm, significantly increase the generation of mitochondrial ROS and the expression of cytokines when compared to larger crystalline silica particles, with a geometric mean of 4.1 μm. Conclusion In summary, this study presents novel data showing that crystalline silica particles with a geometric mean of 0.3 μm enhance the activation of AM when compared to larger silica particles usually represented in in vitro and in vivo research.